Atmospheric corrosion kinetics and dynamics of electrogalvanized mild steel in southeastern coastal area of China–Pakistan Economic Corridor. Issue 9 (14th April 2020) - Jamil, Ishrat; Bano, Humaira; Castano, Juan G.; Zafar, Faiza; Mahmood, Azhar
Abstract: This study aims to examine atmospheric corrosivity, corrodants, and corrosion products of southeastern coastal area of China–Pakistan Economic Corridor as per ISO protocols 9223 and 9225, and ASTM standards G1, G50, G140‐02, D4458‐94, and D2010. Test sites are located at National Institute of Oceanography (NIO) and Karachi Port Trust (KPT) at the banks of the Arabian Sea. Electrogalvanized mild steel test coupons were exposed, and levels of corrodants (sulfur dioxide, chloride, and time of wetness) were measured for a period of 24 months, from May 2014 to May 2016. Corrosivity category C5+ is established in terms of the corrosion rate for both NIO and KPT test stations, which does not coincide with the corrosivity category C5 ascertained by employing environmental characteristics and atmospheric corrodants. Corrosion kinetic parameter " n " and correlation coefficient ( R 2 ) are 0.71 and 0.97 for NIO and 0.96 and 0.97 for KPT, respectively. Scanning electron microscopy/energy‐dispersive spectroscopy, Fourier‐transform infrared spectroscopy, and X‐ray diffraction spectroscopy have corroborated the presence of simonkolleite and hydrozincite, zinc oxide, zinc hydroxychloride, and zinc in corrosion products at both test sites. Abstract : This study classifies the corrosivity category of atmospheric conditions prevailing in Karachi city, an industrial hub and a key part of China–Pakistan Economic Corridor, by employing ASTM and ISO standards that complement spectroscopic techniques. Corrosivity category C5+ in terms of the corrosion rate and C5 in terms of environmental characteristics and atmospheric corrodants are established.